DESIGNING, DEVELOPMENT AND EVALUATION OF GASTRORETENTIVE FLOATING HBS SYSTEM OF METFORMIN: IN VITRO IN VIVO STUDIES - SAMANTA, RADHESHYAM; TIWARI, GAURAV; GUPTA, NAVEEN; RAJPUT, DHARMENDRA SINGH (International Journal of Applied Pharmaceutics, 2024)
Objective: The main objective of this study is to formulate, characterized and evaluate the Medium Molecular Mass Chitosan (MMMCH) – Xanthan Gum (XG) based polymeric carrier mediate of non-effervescent floating hydrodynamically Balanced System (HBS) capsule of metformin for developed stomach specific sustain drug delivery over a prolong periods of time. Methods: Different capsules of metformin were formulated by physical blending of metformin with polymeric mixture to encapsulate in 000 a single unit hard gelatine capsule, than evaluate the different parameters like micromeritics properties, weight uniformity, drug content uniformity, in vitro drug release with their kinetics model, DSC and FTIR study, in vitro in vivo floating characteristic. Results: After evaluating the characteristic properties, it was clearly indicated that excellent value ranges, coefficient of weight variation in between 1.39-2.06%, content uniformity of drug in between 98.23-100.05%, in vitro drug release in between 60–80 % after 12h that can follow Korsmeyer-Peppas model to release the drug no-fiction diffusion method. FTIR and DSC study exhibit no much more incompatibility between drug and polymer and formation of electrolyte complex help to sustaining release over a prolong periods of time. In vitro and in vivo floatation study, it was clearly indicated that all formulation (especially MC4) floated in gastric content more than 12h without any floating lag time and excellent in vivo buoyancy by the help of x ray images of animal model by replacing the drug with barium sulphate. Conclusion: So this type of formulation showing great gastroretentive floating drug delivery system in future with another drugs for a prolong periods of time.